ANALYSIS OF CASH FLOW REPORTS IN ASSESSING FINANCIAL PERFORMANCE AT THE PESISIR SELATAN DISTRICT HEALTH OFFICE - Desmiwerita; Ebit Bimas Saputra (Dinasti Publisher, 2019)
The Pesisir Selatan District Health Office Technical Implementation Unit that has been determined to apply the Financial Management Pattern of the BLUD Work Unit is given in the form of flexibility or flexibility to apply sound business practices to optimally improve health services to the community. Testing the hypothesis in this paper by using a comparison of the value of the test sign with the test table sign. The results of the study found (1) The evaluation of cash flow performance through the current liability ratio in the South Pesisir District Health Office is not good, so the department is unable to pay its current liabilities using only operating cash flow. (2) Evaluation of cash flow performance through the capital expenditure ratio shows quite good results from year to year so there is no need to wait for external funding such as creditors and investors. However, in the last 2 years, there has been a decline so external funding is needed. (3) The evaluation of cash flow performance through debt expenditure ratios at the South Coastal District Health Office is not good. The company does not have a good ability to pay all of its obligations using cash flow originating from the company's normal operating activities and (4) The results of the answers to the second problem found in the South Pesisir District Health Office have applied to account by PSAP and Government Regulation Number 71 of 2010 both in terms of Operating Activities, Non-Financial Asset Investment Activities, Financing Activities, and Non-Budget Activities.